Comparison between Escitalopram and Pregabalin for Generalized Anxiety Disorder Treatment - Zafar, Muhammad Shoaib; Idrees Chaudhary, Nazish (Journal of University College of Medicine and Dentistry, 2022)
Objective: To facilitate the emerging need for investigating the efficacy of escitalopram compared to pregabalin for treating generalized anxiety disorders. Methods: This quasi-experimental study with pre and post-test design was carried out for twelve weeks in the year 2019 between January to June where 90 patients visiting Mayo Hospital in Lahore, within the age range of 18 to 60 years were divided into 2 equal groups by purposive sampling. The 20 mg dose of escitalopram per day was given to the participants of group A while a dose of 150-200mg per day of pregabalin was given to group B and the level of anxiety before and after the experiment was measured by Hamilton Anxiety Baseline. A record of all clinical signs and symptoms was also maintained throughout the time of medication. After 12 weeks, follow-up data was taken from the patients and the scores were compared with the baseline. Results: Efficacy, defined as ≥2% reduction in the scores of anxiety among the participants after 12 weeks was significantly higher in Escitalopram group A than in Pregabalin group B: (92.8% vs. 82.5%) with p-value= 0.003. Gastrointestinal symptoms were seen in 11.9% of patients in Group A and 27.5% of patients in Group B. In Group A 14.2% of patients reported headaches, as compared to 22.5% of patients in Group B. Sleep disturbances, were reported by 10% of patients in Group A and 15% of patients in Group B. Sweating was seen by 19% of patients in Group A and 50% patients in Group B. Urinary symptoms were experienced by 4.7% patients in Group A and 7.5% patients in Group B. Conclusion: Escitalopram is a better option and efficacious for the Pakistani population in treating psychological issues including depression, bipolar and other affective disorders despite the minor side effects compared to Pregabalin.